2016
DOI: 10.1097/tp.0000000000000981
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid Protects Against Ischemia-Reperfusion Injury in Simultaneous Kidney-Pancreas Transplantation

Abstract: These results show that ALA preconditioning is capable of reducing inflammatory markers while decreasing early kidney dysfunction and clinical posttransplant pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…These findings are consistent with our previous work . We showed that ALA treatment to the donor and the recipient have better short‐term outcomes than those where only the transplant recipient was treated with ALA .…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with our previous work . We showed that ALA treatment to the donor and the recipient have better short‐term outcomes than those where only the transplant recipient was treated with ALA .…”
Section: Discussionsupporting
confidence: 93%
“…For instance, preconditioning or postconditioning with ALA is protective against I/RI-induced cardiac dysfunction, retinal damage, ovarian torsion injury and reperfusioninduced renal failure [25][26][27][28]. The latest clinical research has uncovered that the protective mechanisms of ALAP against simultaneous kidney-pancreas transplantation-induced renal dysfunction and post-transplant pancreatitis occur through its anti-inflammatory effects [29]. In our study, ALAP decreased the content of TNF-α and IL-6 and increased the content of IL-10 in rat brains, providing further evidence that the neuroprotective effects of ALAP against cerebral I/RI may be closely related to the synergistic inhibition of the inflammatory response and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent study demonstrated that alpha-lipoic acid may protect against ischemia-reperfusion injury in patients undergoing kidney and pancreatic transplant. 11 We also used alpha-lipoic acid and observed no adverse effects in 8 patients who had undergone renal transplant.…”
Section: Discussionmentioning
confidence: 99%